Building bridges: coauthoring a class handshake, building a classroom community. (2nd October 2018) - Boyd, Maureen P.; Jarmark, Christopher J.; Edmiston, Brian
ABSTRACT: Collaborative social practices that people participate in to coauthor, or co-create, support, and sustain, a classroom community are challenging to research and represent because they are fluid and emergent, and interdependent and cumulative, as they develop across time and space, across experiences and relations. In this article, we take a year-long look at how a weekly whole class greeting ritual, a Class Handshake, serves as a socio-epistemic-embodied-community building practice . We provide a rich description of the dialogic what and how of the Class Handshake ritual, and articulate connections between the Class Handshake and other classroom values and practices. We explore ways this collaborative social practice enacted values and relations that anchored a dialogic teaching and learning stance in this classroom community. We find that the Class Handshake functions like a "polyphonic web, " manifesting and perpetuating a sense of "We"-ness of this classroom community of practice. This study adds to classroom literature that considers dialogic stance and dialogic teaching and learning practices across time. Importantly, this sociocultural discourse analytic study extends attention beyond procedural moves to a big picture examination of purposeful, accretive, and coherent orchestrations of collaborative practices and relations that, together and across time, build classroom community.